Computer Simulation of Control of High-Order Nonlinear Systems using Feedback - Bakhadirova, Gulnaz; Tasbolatuly, Nurbolat; Tanirbergenova, Alua; Dautova, Aigul; Akanova, Akerke; Ulikhina, Yuliya (Bright Publisher, 2024)
The relevance of the topic stated in this research is the need to develop and implement methods of computer modelling of these control systems. The purpose of this research is the search for opportunities for controlling nonlinear systems and the creation of a computer model for controlling nonlinear systems. The basis of the methodological approach in this research work is a combination of methods of theoretical and applied research of general principles of construction of computer models of control of high order nonlinear systems by means of feedback. In the course of the research work, the results were obtained, indicating the effectiveness of the development of an algorithm for finding the control of tracking a given reference signal of nonlinear systems and nonlinear systems with time delay. An algorithm has been developed to find a control that can effectively track the output signal of a nonlinear system behind a given reference signal. In addition, a scientific analysis of the tracking and stabilization errors of nonlinear systems and time-delayed nonlinear systems has been carried out depending on the control parameters, and graphical representations of a computer model of numerical experiments performed according to the control algorithms have been presented. It is established that the output control problem for a nonlinear system is to obtain a feedback control that forces the controlled output signal of the nonlinear system to asymptotically track the reference signal. The practical significance of the obtained results lies in the possibility of their use in the creation of computer models of process control with feedback.